Comparative Efficacy of Preoperative, Postoperative, and Perioperative Treatments for Resectable Colorectal Liver Metastases: A Network Meta-Analysis - Huang, Chao; Huang, Jun; Luo, Hongliang; Zong, Zhen; Zhu, Zhengming (Frontiers in Pharmacology, 2019)
Background: Several treatment strategies are used for management of resectable colorectal liver metastases (CRLMs). We performed a Bayesian network meta-analysis (NMA) to compare preoperative, postoperative or perioperative treatments, identifying the optimal approach. Methods: We searched reports of randomized controlled trials (RCTs) through the relevant databases. The primary outcome criterion was overall survival (OS). The secondary outcome measure was disease-free survival (DFS). We calculated the hazard ratio (HR) with the 95% credible interval (Crl) of the time-to-event data. Rank probabilities were evaluated by the probability of treatment rankings. Multiple treatment comparisons based on a Bayesian network integrated the efficacy of all included approaches. Results: Twenty-two eligible RCTs with 6115 patients were included in the NMA. One treatment that resulted in a significant improvement in OS compared with surgery alone was hepatic arterial infusion (HAI) plus postoperative chemotherapy (CT) [HR = 0.74 with 95% Crl: (0.60, 0.94)]. With regard to the secondary outcome measure, three approaches that led to a significant improvement in DFS compared with surgery alone were HAI plus postoperative CT [HR = 1.44 with 95% Crl: (1.19, 1.75)], postoperative CT [HR = 1.14 with 95% Crl: (1.01, 1.29)], preoperative hepatic and regional arterial chemotherapy (PHRAC) plus preoperative CT [HR = 1.41 with 95% Crl: (1.03, 1.89)]. According to the results for the rank probabilities of the eleven treatments, the combination of HAI and bevacizumab (BEV) plus postoperative CT showed the highest probability of benefitting OS, and PHRAC plus preoperative CT was most likely to benefit DFS. Conclusions: The combination of HAI and BEV plus postoperative CT exhibited the greatest odds of being the most effective treatment for improving OS, and PHRAC plus preoperative CT exhibited the greatest odds of improving DFS. Further clinical studies are needed and justified. Keywords: Colorectal liver metastasis, Hepatic arterial infusion, Chemotherapy, Overall survival, Disease-free survival, Network meta-analysis